2007
DOI: 10.1080/09638280600947922
|View full text |Cite
|
Sign up to set email alerts
|

Interception of moving objects while walking in children with Spastic Hemiparetic Cerebral Palsy

Abstract: Purpose. The purpose of the study was to examine the coordination of reaching and walking behaviour when children with Spastic Hemiparetic Cerebral Palsy (SHCP) intercept an approaching and hence externally-timed object. Method. Using either the impaired or non-impaired arm, children intercepted a ball approaching from a fixed distance with one of three velocities. Each participant's initial starting position was scaled to their maximum walking velocity determined prior to testing; for the medium ball velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These effects increased in children [11,12,14]. Other studies showed that CP children were perfectly able to adapt to stimulus velocity by varying movement time without significantly changing the time of movement initiation [15,16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These effects increased in children [11,12,14]. Other studies showed that CP children were perfectly able to adapt to stimulus velocity by varying movement time without significantly changing the time of movement initiation [15,16].…”
Section: Discussionmentioning
confidence: 94%
“…However, this behavior may be of importance to improve the rehabilitation process, considering the numerous daily life situations in which anticipation-coincidence may be involved, such as playing music, catching a ball, avoiding a moving obstacle, etc. For instance, it has been shown that CP children developed specific adaptations to compensate for their sensory-motor deficits and to provide correct behavioral responses when performing a task requiring to walk at various velocities for catching a stationary or moving ball [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…found that range of motion of the impaired arm when banging a drum was larger than when instructed to extend as far as possible. It is clear that relevant and challenging task demands facilitate children with USCP to exploit fully the available degrees of freedom to achieve optimal movement solutions …”
Section: The Use Of Degrees Of Freedom In Walking and Reachingmentioning
confidence: 99%
“…It is clear that relevant and challenging task demands facilitate children with USCP to exploit fully the available degrees of freedom to achieve optimal movement solutions. 7,10,14 Musculoskeletal system DOFs…”
Section: The Use Of Degrees Of Freedom In Walking and Reachingmentioning
confidence: 99%
See 1 more Smart Citation